Kabar Sunda Program Reduces Aggressive Behavior in Elementary Students: Program Kabar Sunda Menurunkan Perilaku Agresi Siswa Sekolah Dasar - Nurrahmah, Rara; Pratiwi, Anggia Suci; Lestari, Asti Tri; Dewi, Rikha Surtika (Indonesian Journal of Innovation Studies, 2026)
General Background: Aggressive behavior among elementary students disrupts learning activities and hinders social-emotional development in classroom environments. Specific Background: This condition was found in a third-grade student at SDN 1 Puspahiang, exhibiting physical, verbal, emotional, and hostile aggression, requiring contextual interventions aligned with Sundanese cultural values. Knowledge Gap: Although character education and cultural-based learning are theoretically recommended, practical implementation in schools remains limited, particularly programs integrating Kaulinan Barudak Sunda for behavioral regulation. Aims: This study aims to identify forms of aggression demonstrated by the student and to apply the Kabar Sunda (Kaulinan Barudak Sunda) Program as a strategy for reducing aggressive behavior. Results: A qualitative case study was conducted using participatory observation, in-depth interviews, and documentation over five traditional game sessions. Findings indicate aggressive behavior across dimensions conceptualized by Buss and Perry, triggered by internal emotional frustration and external disharmonious interactions, with aggression reduction reaching approximately 70–80% and improvement in rule compliance, participation, cooperation, and social interaction. Novelty: This research introduces a culturally grounded intervention through traditional Sundanese games as a contextual, engaging mechanism for behavioral regulation in early education settings. Implications: The outcomes offer a practical alternative for schools to employ local cultural assets as sustainable character-building strategies, reinforcing values of silih asih, silih asah, and silih asuh while fostering a conducive learning climate. Highlights Aggressive behavior decreased progressively across five sessions of traditional Sundanese games. Cultural values integration supported improvements in compliance, cooperation, and interaction. Localized educational programs created a meaningful alternative for character development. KeywordsAggressive Behavior; Elementary Students; Kabar Sunda Program; Traditional Games; Local Culture